Unveiling a New Association: First Record of Psocoptera in Social Wasp Nests - Bruno C. Barbosa; Tatiane T. Maciel; Daniel M. Lima (Entomological Communications)
Social wasp nests provide stable microhabitats that can support diverse arthropod communities. This study reports the first record of psocopterans associated with social wasp colonies, highlighting a potential commensal relationship. We analyzed 88 colonies and nests between 2016 and 2018 in secondary urban forest fragments in Brazil. A total of 219 psocopterans were recorded in 15 nests, with Liposcelis bostrychophila Badonnel, 1931 being the most abundant species. The presence of nymphs and adults in both active and abandoned nests suggests that these insects exploit the nests regardless of colony activity. These findings emphasize the role of social wasp nests as important microhabitats and provide new insights into the ecological interactions within these structures, contributing to a broader understanding of arthropod biodiversity.